93.2k views
2 votes
F(x)=-x^2+3 find f(-2)​

User HammerFet
by
4.4k points

1 Answer

5 votes

Answer:

f(-2) = - 1

Explanation:

you could begin by understanding that f(x) is an alternate and informative version of y = -x^ + 3

The difference (critical) is that f(x) tells you how to substitute for x on the right.

You need to pay attention to doing something with - 2

f(-2) = - (-2)^2 + 3

Notice what you did. Wherever there is an x on the right, you put in a -2.

f(-2) = - (4) + 3

f(-2) = - 1

User Matinict
by
5.0k points